2022
DOI: 10.3390/ani12131669
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Performance, Nutrient Digestibility, Gut Bacteria and Bone Strength of Broilers Offered Alternative, Sustainable Diets Varying in Nutrient Specification and Phytase Dose

Abstract: This study assessed the use of locally sourced sustainable feed ingredients, rapeseed meal (RSM) and maize dried distiller grains with solubles (DDGS) in diets over traditional ingredients on the growth performance, bone strength and nutrient digestibility of broilers. This work also investigated the effects of supplementing exogenous phytase in two doses (500 vs. 1500 FTU/kg). Using male Ross 308 chicks (n = 320) assigned to receive one of four experimental diets: (1) Positive control diet 1 (PC1), a wheat, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…Phytase inclusion decreased excreta P concentration by approximately 27%, which could be, to a major extent, attributed to the releasing effect of phytase enzyme on PAbound P, and it leads us toward more environmentally sustainable broiler production. Similar to current results, Mulvenna et al [48] reported a 20% reduction during 0-28 d on a g/kg BW gain basis and a reduction of 15% in total P excretion to 2.2 kg target weight in broilers fed phytase-supplemented diets.…”
Section: Discussionsupporting
confidence: 90%
“…Phytase inclusion decreased excreta P concentration by approximately 27%, which could be, to a major extent, attributed to the releasing effect of phytase enzyme on PAbound P, and it leads us toward more environmentally sustainable broiler production. Similar to current results, Mulvenna et al [48] reported a 20% reduction during 0-28 d on a g/kg BW gain basis and a reduction of 15% in total P excretion to 2.2 kg target weight in broilers fed phytase-supplemented diets.…”
Section: Discussionsupporting
confidence: 90%
“…This might be attributed to the potential role of Zymomonas mobilis making more nutrients available for growth. This was in agreement with the observation of Mulvenna et al (2022) who reported that a traditional soya-based diet with commercial exogenous phytase resulted in the best growth response in broiler chickens. However, this report was contrary to the observation of Biesek et al (2020) who reported that broiler finishers fed legume seeds and rape seed meal have significantly reduced body weight gain and increased feed conversion ratio in the experimental groups than the control group fed soyabean meal based diet.…”
Section: Performance Characteristics Of Finishing Broiler Chickens Fe...supporting
confidence: 93%
“…This agreed with the reports of Hartinger et al (2022), who reported higher body weight, average daily gain and improved feed conversion ratio when Hermetia illucens defatted larvae meal-based diets were fed to Ross 308 broiler chickens as a protein source. Several similar reports have been observed in earlier studies (Janocha et al, 2022 andMulvenna et al, 2022). The reduced feed intake in broiler chickens fed 100 % CCZ could indicate the adequacy of the energy content of the diet because birds feed to satisfy their energy need.…”
Section: Performance Characteristics Of Starting Broiler Chickens Fed...supporting
confidence: 81%
“…Bone formation (GO:0060349) encompasses the intricate processes of growth, differentiation, and tissue development in bones, which is meticulously regulated by pivotal factors including bone morphogenetic proteins ( BMPs ), the Wnt signaling pathway, and parathyroid hormone-related peptide ( PTHrP ) ( Li et al, 2009 ). Notably, Mulvenna et al (2022) have demonstrated that manipulating the nutritional specifications and phytase enzyme dosage in broiler chicken feed can exert a discernible impact on the robustness of their skeletal structure. A comprehensive comprehension of the underlying molecular mechanisms governing avian bone formation is essential for investigating skeletal disorders, elucidating bone growth regulation, and enhancing poultry production.…”
Section: Results and Disscussionmentioning
confidence: 99%